Myostatin-like gene: A potential target for gene silencing in giant freshwater prawn, Macrobrachium rosenbergii / Sarasvathi Easwvaran - Sarasvathi , Easwvaran (2016)
Macrobrachium rosenbergii is commonly known as the ‘giant freshwater prawn’, a commercially important cultivable food species of South and Southeast Asia. Growth retardation and diseases hindering growth are few of the important constrains faced by Macrobrachium rosenbergii (Mr), thus highlighting the need of an in-depth study on the growth and growth related genes to improvise this species. Myostatin (MSTN) is an interesting negative growth regulating gene which has been well characterized in vertebrates but studied very little in invertebrates. Thus there is a need to ascertain its functional role more precisely in invertebrates specifically crustaceans. The present study is focused on molecular cloning and characterization of the MSTN gene in M. rosenbergii (MrMSTN) followed by gene profiling at different life stages and upon IHHNV infection. It also focuses on further silencing this gene in Giant freshwater prawn, M. rosenbergii in order to record any histological changes. In addition, the study also deals with the MSTN gene’s influence on other genes of interest related to growth which include myosin heavy chain, dystrophin-dystroglycan complex, tropomyosin, farnesoic acid O methyl transferase, arginine kinase, cyclophilin, and acyl CoA desaturase. We have characterized a full length MrMSTN gene encoding 1619 base pairs (bp) with an open reading frame of 945 bp that encodes 315 amino acid residues. MrMSTN retains all the conserved characteristics which belong to the TGF-β superfamily including the propeptide and mature peptide domain, cysteine residues and a proteolytic cleavage site, RXXR where “XX” denotes Asparagine and Arginine. The bioinformatic analysis confirmed that MrMSTN belongs to the TGF-β superfamily and is evolutionarily conserved especially in the mature peptide domain. MrMSTN gene is ubiquitously expressed in the tested tissues of healthy adults, with the highest expression observed in the muscle. Moreover, the MrMSTN transcripts showed significant (P < 0.05) changes at different life stages of M. rosenbergii as well as in infectious hypodermal and hematopoietic necrosis virus (IHHNV)-challenged prawns. Our histological analysis following the successful MrMSTN dsRNA gene silencing showed the onset of muscle regeneration, thus supporting MrMSTN functional role serving as a negative growth regulator, as similar in vertebrates. Moreover, the MrMSTN also significantly influences the mRNA transcripts of other growth regulating genes, and this activity coincides with a muscle regeneration process that takes place. Our findings, illustrated the role of MrMSTN as a negative growth regulator and its importance in muscle growth and development in M. rosenbergii. The MrMSTN could therefore be a potential target for gene manipulation aimed at enhancing the growth and development of M. rosenbergii. In addition it could also be developed as a biomarker to address the growth deficiency related problems in M.rosenbergii.